The Iranians : Persia, Islam, and the soul of a nation, with a new afterword by the author - Mackey, Sandra, 1937- (New York : Penguin Group, 1998)
Provides a portrait of the troubled nation of Iran and the complex religious, historical, political, and cultural forces--especially the dichotomy between Islam and the culture of ancient Persia--that continue to shape it.
Glory of Persia -- Invasion of Islam -- God and state -- Faces of authority: father, king, and cleric -- King and nation: Iran's first revolution -- Reza Shah: to the glory of the nation -- Shah and the Prime Minister: Iran's second revolution -- Shah and the Ayatollah: Persia and Islam -- Persian empire of Muhammad Reza Shah -- Double revolution -- Internal and external: wars for the Iranian nation -- Islamic government: religion, culture, and power -- Islamic republic of Iran: failed quest for justice.
"A Plume Book"
Includes bibliographical references (pages 421-426) and index.
Keywords: Iran -- Politics and government -- 20th century